Abnormal Liver Function Test during Pregnancy also Determine the Maternal and Fetal Outcomes - Jamil, Shazia; Mahmood, Naveed; Mahmood, Kinza; Imran, Rabiah; Anwaar, Izza; Anwaar, Maheen; Haque, Israr-ul- (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of this study was to look into the clinical profile, incidence, and potential reasons of liver function test abnormalities among pregnant women. Study Design: Prospective/Observational study Place and Duration: Department of Medicine, OMC Hospital, Jail Road Lahore from February, 2020 to June, 2021. Methods: There were one hundred and five pregnant women had liver dysfunction were included. Age of the patients was between 19-45 years. All patients provided written consent before having their demographic data collected, including their age, BMI, gender, and trimester of pregnancy. Association of symptoms among presented patients was also recorded. Females were underwent for liver test to diagnose abnormalities. Prevalence of liver disease abnormalities and maternal outcomes were assessed in this study. We used SPSS 22.0 version to analyze complete data. Results: Mean age of the pregnant females was 26.47±7.49 years and had mean BMI 24.11±3.34 kg/m2. Majority of the patients 60 (57.1%) had parity I. Mean gestational age of the patients was 33.13±5.33 weeks. We found that majority of the patients were in 65 (61.9%) third trimester. Oedema, headache and fever were the most common symptoms presented. Prevalence of abnormal liver function test was among 85 (80.9%) cases. Most common cause was hyperemesis gravidarum found in 57 (54.3%) cases followed by hepatitis in 48 (45.7%) cases. Most common syndrome was HELLP 35 (33.3%) and AFLP in 18 (17.1%) females. Frequency of pre-eclampsia was in 29 (27.6%) cases. C-section was carried out in 36 (34.3%) cases. No maternal mortality found in our study but rate of mortality in fetals were 24 (28.2%). Conclusion: During the third trimester of pregnancy, pregnancy-related illnesses are the most common reason for abnormal liver function tests. Usually, pre-eclampsia is the root of this problem.